2013
DOI: 10.1093/bioinformatics/btt498
|View full text |Cite
|
Sign up to set email alerts
|

A-clustering: a novel method for the detection of co-regulated methylation regions, and regions associated with exposure

Abstract: tsofer@hsph.harvard.edu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 20 publications
(22 reference statements)
1
71
0
1
Order By: Relevance
“…20 Houseman et al, 2012 proposed a statistical model for estimation of blood cell type proportion using methylation data. 61 Using this methodology, they found that the leukocyte distribution accounts for only 3% of the differences in the DNA methylation profile of individuals exposed to arsenic (As).…”
Section: Groupmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Houseman et al, 2012 proposed a statistical model for estimation of blood cell type proportion using methylation data. 61 Using this methodology, they found that the leukocyte distribution accounts for only 3% of the differences in the DNA methylation profile of individuals exposed to arsenic (As).…”
Section: Groupmentioning
confidence: 99%
“…The co-regulated regions can be assigned to specified clusters and the effect of the exposure on these clusters can be tested using the generalized estimating equation (GEE). 20 GEE uses a weighted combination of observation to measure the effect of a covariate (in our case Pb exposure) while conserving the correlation structure of the data. 64 Consequently this approach is much less conservative and yields a greater number of differentially methylated regions compared to the traditional case-control study with a single CpG site b value comparison.…”
Section: Hm450k Bead Chip Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…The samples of the training set were used to fit the linear regression model and to compute the predictor coefficients' estimates are, respectively, the cord blood methylation value and the mean of the correlated nearby cord blood methylation sites from the sample being predicted. The assign.to.clusters function in the R package Aclust [19] was used to define the sets of neighboring CpG sites that are correlated with each other, using default parameters. This function implements a clustering method to discover methylation regions by clustering together adjacent probes within a genomic distance constraint according to their Spearman correlation between samples (within a single tissue).…”
Section: Statistical Models For Prediction Linear Prediction Modelmentioning
confidence: 99%